(untitled) (New York, 2000)
Since publication of the first edition in 1995, there have been significant advances and understanding of chromatin structure and its relation to gene expression. These include a high-resolution structure of the nucleosome core, discovery of the enzymes and complexes that mediate histone acetylation and deacetylation, discovery of novel ATP-dependent chromatin remodeling complexes, insights into nuclear organization and epigenetic silencing mechanisms. In light of these advances, "Chromatin Structure and Gene Expression" includes updated chapters and additional material that introduce concepts in the process of gene regulation in chromatin. This book is intended for researchers and advanced students interested in the effect of chromatin structure on gene expression.
Keywords: Chromatin,Nhiễm sắc thể